Galectin-1 confers immune privilege to human trophoblast: Implications in recurrent fetal loss - Ramhorst, Rosanna Elizabeth (2012)
Mechanisms accounting for protection of the fetal semiallograft from maternal immune cells remain incompletely understood. In previous studies we showed that galectin-1 (Gal1), an immunoregulatory glycan-binding protein, plays key roles in modulating immune responses during murine pregnancies. Here we show that Gal1 fosters immune privilege at the human fetomaternal interface through modulation of multiple tolerance mechanisms. Gal1 was mainly expressed in invasive extravillous trophoblast cells of human first trimester and term placenta in direct contact with maternal tissue. Trophoblast-derived Gal1 was primarily controlled by progesterone and pro-inflammatory cytokines and fostered T cell tolerance by favoring the expansion of CD4+CD25+FoxP3+ regulatory T (Treg) cells, suppressing the secretion of Th1-type cytokines and limiting T cell viability. Targeted inhibition of Gal1 expression through different strategies including Ab-mediated blockade, addition of the specific disaccharide lactose and silencing through retroviral-mediated siRNA strategies prevented these immunoregulatory effects. Consistent with a tolerogenic function for endogenous Gal1, patients with recurrent pregnancy loss showed considerably lower levels of circulating Gal1 and had greatly enhanced frequency of anti-Gal1 autoantibodies in their sera compared with fertile women. Thus, endogenous Gal1 confers immune privilege to human trophoblasts by triggering a broad tolerogenic program, with potential implications in threatened pregnancies.